Civil servants’ readiness for AI adoption: The role of change management in Morocco’s public sector - Mohamed Barodi; Siham Lalaoui (Problems and Perspectives in Management)
The rapid digital transformation of public systems has improved interactions between governments and citizens. In Morocco, while efforts to digitalize public administration continue, the integration of artificial intelligence presents new challenges due to structural and technical limitations. This study explores the openness of Moroccan civil servants to adopting artificial intelligence solutions and examines the role of change management in facilitating this process. A quantitative approach was employed, with 129 civil servants from key ministries – Education, Finance, and Health – completing an online questionnaire. These ministries were selected due to their critical importance in the public system and their frequent interactions with citizens. Furthermore, they played a central role in the National Administrative Reform Plan (2018–2022), which emphasized digital transformation as a key pillar in advancing e-government. The collected data were analyzed using SPSS, enabling a comprehensive analysis of the factors influencing AI adoption. The findings reveal that while younger civil servants are more open to AI, over 40% of respondents pointed to insufficient digital skills as a major barrier to artificial intelligence integration. The study underscores the importance of effective change management strategies, highlighting that strong leadership and clear communication are essential in promoting artificial intelligence receptiveness and ensuring seamless integration within Morocco’s public sector.